The Evaluation of Teachers’ Practices of Project-Based Learning Strategy in Writing Instruction - Rahman, Dian Fathur; Linggar Bharati, Dwi Anggani; Rukmini, Dwi (English Education Journal, 2021)
This research is a qualitative study of the Project-Based Learning (PjBL) practice. PjBL is one of the three main teaching and learning methods suggested in the implementation of the 2013 curriculum. Researches on the teachers’ perception were mostly on the benefits of PjBL, but their understandings of PjBL were commonly ignored. Meanwhile, the teachers’ beliefs and perceptions affect what they do in the classrooms. Their perceptions deeply influence the way they plan, teach, and perform assessments. Therefore, this study is aimed at evaluating how the teachers perceive, plan, implement, and assess PjBL in writing instruction. The result of this study is expected to enrich the practical concept and theory of PjBL. Besides, it is important for the readers, especially the teachers to either revise or improve their perception, knowledge, and understanding of PjBL, especially in writing instruction. To collect the data, the researcher used a questionnaire, document, classroom observation, and interview. The findings show that the teachers have several incorrect perceptions of PjBL. Their misperceptions lead them to make inappropriate PjBL plans, implementations, and assessments. Accordingly, it reveals the teachers’ perceptions of PjBL were compatible with their PjBL plan, implementation, and assessment. However, this compatibility did not show the appropriateness of the teachers’ PjBL practice due to several misperceptions of PjBL of the teachers.